Efektivitas Kombinasi Prenatal Yoga Berbasis Audiovisual Dan Balsem Lavender Untuk Mengatasi Low Back Pain Pada Ibu Hamil Trimester III - Ni Made Dewianti; Fitria Fitria; Kadek Widiantari; Ni Made Ari Febriyanti; Ni Ketut Ayu Sugiartini (Direktorat Politeknik Kesehatan Makassar, 2025)
The most common complaint experienced during the third trimester of pregnancy is low back pain (LBP). Low back pain during pregnancy is described as pain in the lumbar region, above the sacrum, and this pain can radiate to the legs. The pain is often dull in nature and worsened by flexion of the lumbar spine toward the anterior. Efforts that can be made to minimize LBP complaints in pregnant women in the third trimester include relaxation techniques and breathing exercises, hydrotherapy, Transcutaneous Electrical Nerve Stimulation (TENS), massage, behavioral techniques, hypnotherapy, therapeutic touch, yoga, and the application of balm. The aim of this study was to analyze the effectiveness of a combination of audiovisual-based prenatal yoga and lavender balm in reducing LBP in pregnant women in the third trimester. The study design was analytical with a two-group design including a control group, with a sample size of 60 participants. The sampling technique used was purposive sampling. Data analysis was performed using paired t-tests and independent t-tests. The results showed that the mean LBP value before intervention in the treatment group was 6.25 and the mean LBP value in the control group was 6.01 with a p-value of 0.345. The mean LBP value after intervention in the treatment group was 3.45 and the mean LBP value in the control group was 7.65 with a p-value of 0.00. Based on bivariate data analysis, the p-value was 0.000. The combination of prenatal yoga based on audio-visual materials and lavender balm was effective in reducing LBP in pregnant women in the third trimester. Recommendations include the regular practice of prenatal yoga for pregnant women and the use of balm to reduce LBP complaints in pregnant women. Keywords: Prenatal yoga; lavender balm; lower back pain; pregnant women